Functionalization of WS2 Nanotubes with Fluorescent C‐dots and Conductive Polythiophenes. Issue 7 (1st March 2019) - Kumar, Vijay Bhooshan; Harel, Yifat; Ben‐Ishay, Rivka; Lellouche, Jean‐Paul; Gedanken, Aharon
Abstract: Multifunctional nanoparticles have attracted significant interest for their multifunctional applications. Described herein is the building of a new hybrid nanocomposite particle, conjugating tungsten disulfide (WS2 ) nanotubes (NTs) to fluorescent carbon dots (C‐dots). Hybrid WS2 ‐C‐dots hyb‐NTs nanomaterials are prepared by a hydrothermal reaction of PEDOTAc ‐WS2 NTs, where the PEDOTAc (poly 2, 3‐dihydrothieno[3, 4‐b][1, 4]dioxine‐2‐carboxylic acid) polymer serves as the C‐dots precursor. The physical and chemical properties of the as‐synthesized WS2 ‐C‐dots hyb‐NTs are determined by X‐ray powder diffraction (XRD), transmission electron microscopy (TEM), CHNSO analysis, and fluorescence, Raman, and UV–vis absorption spectroscopy. The WS2 ‐C‐dots hyb‐NTs are shown to be very stable at normal room temperature and pressure and could be useful for multicolor cell imaging and targeted cell killing. Abstract : This work describes the building of a new hybrid nanocomposite particle, conjugating tungsten disulfide (WS2 ) nanotubes (NTs) to fluorescent carbon dots (C‐dots). The WS2 ‐C‐dots hyb‐NTs are very stable at normal room temperature and pressure, and could be useful for multicolor cell imaging and targeted cell killing.